Lipids and α-Synuclein: adding further variables to the equation - Schepers, Jana; Löser, Timo; Behl, Christian (Frontiers in Molecular Biosciences, 2024)
Aggregation of alpha-Synuclein (Syn) has been connected to several neurodegenerative diseases, such as Parkinson’s disease (PD), dementia with Lewy Bodies (DLB), and multiple system atrophy (MSA), that are collected under the umbrella term synucleinopathies. The membrane binding abilities of Syn to negatively charged phospholipids have been well described and are connected to putative physiological functions of Syn. Consequently, Syn-related neurodegeneration has been increasingly connected to changes in lipid metabolism and membrane lipid composition. Indeed, Syn aggregation has been shown to be triggered by the presence of membranes in vitro, and some genetic risk factors for PD and DLB are associated with genes coding for proteins directly involved in lipid metabolism. At the same time, Syn aggregation itself can cause alterations of cellular lipid composition and brain samples of patients also show altered lipid compositions. Thus, it is likely that there is a reciprocal influence between cellular lipid composition and Syn aggregation, which can be further affected by environmental or genetic factors and ageing. Little is known about lipid changes during physiological ageing and regional differences of the lipid composition of the aged brain. In this review, we aim to summarise our current understanding of lipid changes in connection to Syn and discuss open questions that need to be answered to further our knowledge of Syn related neurodegeneration.